ANDROID APPLICATION OF MIDDLE-SMALL BUSINESS MAPPING (UKM) IN TEGAL CITY BASED ON GEOGRAPHIC INFORMATION SYSTEM (GIS) AND LOCATION-BASED SERVICE(LBS) - Indriyanto, Jatmiko; Bukhori, Imam; Budihartono, Eko (International Journal of Research -GRANTHAALAYAH, 2019)
Researchers began to research UKM, Tegal City Cooperative Service and region in Tegal City, researchers found in UKM, a location that has businesses in various places in the village, especially regarding UKM. However, many of these UKM locations are unknown to the public. One problem is the lack of data regarding the address and location of UKM. So now it is very much needed an android application using GIS and LBS that will facilitate and help the people of Tegal to be able to obtain data and find out more about UKM in the city of Tegal. Google Maps is an application on Android smartphones and computers that can be accessed via the internet so that Google Maps can display on Android. The purpose of this study is to facilitate the Tegal community to find information on locations, products, and UKM owners, based on a survey by researchers. The implementation of the UKM location mapping system in the city of Tegal will certainly make it easier for the people of Tegal to find data about the addresses and products of UKM in the city of Tegal. Because every data needed becomes more accurate, fast and efficient.